Business plan: atoque bundle / Ahmad Farid Imran Dzulkipli...[et al.] - Dzulkipli, Ahmad Farid Imran; Mohd Zaini, Muhamad Harith; Asakir, Muhammad Shahmi; Mat Aris, Aiman Danial (2019)
Atoque Bundle is a pre-loved apparel business that focus on selling pre-loved items. Based in SS15, Subang Jaya, we supply and sell pre-loved materials from variety kind of brands including Nike, Puma, Adidas, Fila and more. The vision of Atoque Bundle is to be the best supplier of pre-loved apparels in clothing industry. The mission is to achieve the target sale. For the marketing, we choose the Internet and social media network such as Carousell, Facebook and Instagram as a platform of communication to our customers all around Malaysia. As for the demand, it seems as it is progressively grew as more people likely choose buying stuffs from the social media, the demand buying pre-loved items is increasing drastically due to the young generations that love to go with stylish clothing with affordable price. Also, the apparels we are selling are usually the cheap ones but there's still available the expensive ones with such rare, limited edition shoes that store like us resells. The price of product are affordable and reasonable for people to buy. Our target customers is not limited to student of INTI College but also people walking by can walk-in and have a little sight-seeing for some good stuffs here. To boost our sales, we do promotions such as the Black Friday sales. For the start of this business, we needed at least full commitment of teamwork and financial support from each one of us. We started from a small business that goes online on instagram, promoting pre-loved items that we are selling to a fast grown sales based in Subang Jaya. Froiii this business, we learnt about the bravery and the dare to take the risks in order to achieve our goals and target sales. From this business, it also give us the chance to improve our communication skills with the customer, this platform of social media that has lot to offer is the best place to start making improvement to ourselves and our relationship with the customers. Last but not least, this business has been a good platform to outstand our true potential on becoming a future entrepreneur.